Zoonotic Ancylostoma ceylanicum Infection Detected by Endoscopy - Ngui, R.; Lim, Y.A.L.; Wan Hafiz, W.I.; Lim, K.N.; Mahmud, R. (American Society of Tropical Medicine and Hygiene, 2014)
We report a case of Ancylostoma ceylanicum infection detected by endoscopy. It was diagnosed and confirmed using polymerase chain reaction (PCR) and DNA sequencing. The patient is a 58-year-old Malaysian woman who lives in a rural area, where uncontrolled populations of stray and semidomesticated dogs live in close proximity with humans.